Odpowiedzi

2010-01-31T00:01:10+01:00
A= -3 b= 6
2a+(-4a)²-(-13b+6)+[(14b+3a)+(-12b-7b)]=2a+16a²+13b-6+[14b+3a-12b+7b]=2a+16a²+13b-6+14b+3a-12b+7b=5a+16a²+8b-6=5*(-3)+16*(-3)²+8*6-6=-15+144+48-6=171
2010-01-31T00:02:05+01:00
A= -3 b= 6
2a+(-4a)²-(-13b+6)+[(14b+3a)+(-12b-7b)]=
=2a+16a²+13b-6+[14b+3a-12b-7b]=
=2a+16a²+13b-6+3a-5b=
=16a²+5a+8b-6

16a²+5a+8b-6=16(-3)²+5(-3)+8*6-6=16*9-15+48-6=144-15+42=171

Najlepsza Odpowiedź!
2010-01-31T00:06:17+01:00
A= -3 b= 6

2a + (-4a)² - (-13b+6) + [(14b +3a) + (-12b-7b)] =
= -6 + 144 + 78 - 6 + 84 - 9 - 72 - 42 = 171